Surviving and Thriving: An Introduction to Childhood and Youth Post-Disaster Recovery in the Context of the Canterbury Earthquakes of 2010-2012 - Mooney, Maureen F; Johal, Sarb; Paton, Douglas; Tarrant, Ruth; Johnston, David (School of Psychology, Massey University, 2012)
Potentially traumatic experiences, such as disasters, represent particularly complex experiences. While generally agreed that adversity has definite effects at a population level, the nature of these effects is open to debate. Past research has tended to focus on vulnerability and trauma. However, recent research suggests that experiencing adversity can sometimes be resolved in terms of enhanced well-being, and capacities to adapt. The specific focus of this paper is on children and youth, as there has been minimal research on how models of adaptation and accommodation in adults may apply to young people. The study seeks to further understanding of factors and processes that promote positive coping, adaptation, and wellbeing. It will examine adaptation using a study of experience over the course of a recovery process. A repeated measures approach will examine recovery processes, including resilience and post-traumatic growth. It is hoped that results will inform future preparation for adversity, and increase support to children and youth recovering from challenging life experiences, including disasters.
This work is licensed under a Creative Commons Attribution-NonCommercial-NoDerivs 3.0 Unported License.
Keywords: Childhood recovery; Disaster; Post-traumatic growth; Resilience; Positive coping